Lateral Flow Loop-Mediated Isothermal Amplification Test with Stem Primers: Detection of Cryptosporidium Species in Kenyan Children Presenting with Diarrhea - Timothy S. Mamba; Cecilia K. Mbae; Johnson Kinyua; Erastus Mulinge; Gitonga Nkanata Mburugu; Zablon K. Njiru (Journal of Tropical Medicine)
Background. Cryptosporidium is a protozoan parasite and a major cause of diarrhea in children and immunocompromised patients. Current diagnostic methods for cryptosporidiosis such as microscopy have low sensitivity while techniques such as PCR indicate higher sensitivity levels but are seldom used in developing countries due to their associated cost. A loop-mediated isothermal amplification (LAMP) technique, a method with shorter time to result and with equal or higher sensitivity compared to PCR, has been developed and applied in the detection of Cryptosporidium species. The test has a detection limit of 10 pg/µl (~100 oocysts/ml) indicating a need for more sensitive diagnostic tools. This study developed a more sensitive lateral flow dipstick (LFD) LAMP test based on SAM-1 gene and with the addition of a second set of reaction accelerating primers (stem primers). Results. The stem LFD LAMP test showed analytical sensitivity of 10 oocysts/ml compared to 100 oocysts/ml (10 pg/ul) for each of the SAM-1 LAMP test and nested PCR. The stem LFD LAMP and nested PCR detected 29/39 and 25/39 positive samples of previously identified C. parvum and C. hominis DNA, respectively. The SAM-1 LAMP detected 27/39. On detection of Cryptosporidium DNA in 67 clinical samples, the stem LFD LAMP detected 16 samples and SAM-2 LAMP 14 and nested PCR identified 11. Preheating the templates increased detection by stem LFD LAMP to 19 samples. Time to results from master mix preparation step took ~80 minutes. The test was specific, and no cross-amplification was recorded with nontarget DNA. Conclusion. The developed stem LFD LAMP test is an appropriate method for the detection of C. hominis, C. parvum, and C. meleagridis DNA in human stool samples. It can be used in algorithm with other diagnostic tests and may offer promise as an effective diagnostic tool in the control of cryptosporidiosis.